Community knowledge, attitude, and practice, incidence of suspected cases, and epidemiological distribution of rabies in humans and animals in Southwest Shewa zone, Oromia, Ethiopia - Dinbiso, Tegegn Dilbato; Mekonnen, Abebe Tibebu; Olana, Tolesa Negasa; Ayana, Gudina Mekonnen; Kelbesa, Kebede Abdisa; Deso, Hana Dejene; Gudina, Segni Bedasa; Biru, Moges Kidane; Hordofa, Mulatu Ayana; Berecha, Mekonnen Sorsa (Frontiers in Veterinary Science, 2025)
BackgroundRabies remains a major public and veterinary health problem in most developing countries, including Ethiopia. Despite its importance in public health, no systematic study has been conducted in the area. Therefore, this study aimed to assess the knowledge, attitude, and practice and to estimate the incidence and spatial distribution of rabies in humans and animals in the Southwest Shewa zone of Oromia, Ethiopia.MethodsA questionnaire-based cross-sectional and retrospective study designs were employed among 422 randomly selected informants potentially at risk of rabies. Data were collected using a semi-structured questionnaire. The study utilized retrospective data from individuals admitted for rabies between 2017 and 2021 to analyze and map the epidemiological distribution of the disease using ArcGIS. Furthermore, descriptive statistics and logistic regression models were employed to analyze the data.ResultsThis study revealed that the level of good knowledge, positive attitude, and good prevention practices toward rabies among the communities was 58.3, 47.9, and 54.2%, respectively. The proportion of respondents who own dogs (OR = 1.7, 95% CI: 1.050–2.873, p = 0.032), live in urban areas (OR = 10.7, 95% CI: 1.106–103, p = 0.042), and have a higher degree of education (OR = 2.4, 95% CI: 1.061–5.513, p = 0.036) were statistically significantly associated with good knowledge scores toward rabies. Private workers and urban residents were statistically associated with positive attitude scores on rabies (p < 0.05). Living in urban areas (OR = 2.9, 95% CI: 1.596–5.407, p = 0.000) and Weliso district (OR = 10, 95% CI: 4.099–24.560, p = 0.000) had good prevention practice scores toward rabies. A total of 529 suspected rabies cases with an overall incidence of 44.9 cases per 100,000 population in humans and 127 suspected rabies cases with an overall incidence of 3.4 cases per 100,000 population in animals were registered from 2017 to 2021.ConclusionThe level of knowledge, positive attitude, and good practice toward rabies was found to be inadequate. Therefore, awareness creation programs and effective and well-organized prevention and control measures should be employed, with a special focus on identified risk factors, to reduce disease burdens through a One Health (OH) approach.